Impact of Foreign Direct Investment on Economic Growth of Nepal - Pokharel, Shiva Prasad; Pokharel, Bishnu Prasad (Tribhuvan University Journal, 2019)
This paper aims to investigate the impact of Foreign Direct Investment (FDI) on the economic growth of Nepal for the period 2008/09 to 2017/18 A.D. yearly data. It evaluated the Gross Domestic Product (GDP) performance and the trends of FDI and Gross Fix Capital Formation (GFCF) in Nepal. To demonstrate the relationship between Nepalese Gross Domestic Product (GDP) and Foreign Direct Investment (FDI) and Gross Fix Capital Formation (GFCF) Multiple-Regression-Model has been applied along with various econometrics techniques such as Unit-Root Test, Granger-Causality Test and Ordinary Least Square (OLS). GDP in this model is used as dependent variable whereas FDI and GFCF are measured as independent variables. According to the results, Unit Root Test indicated that all the variables included in the model were not stationary at level except FDI, whereas GDP and GFCF are stationary at first difference. The model is overall significant with the positive and significant relationship of GDP, FDI and GFCF. Result also indicate a good fit for the model with R2=86%. The Granger Causality Test revealed that there was no causality between the variables since all p-value obtained are more than 5%. Based on the empirical result of this paper, policy recommendation proposed that for Nepal to generate more foreign direct investment, hard work should be made at solving problems of government involvement in business; relative closed economy; corruption; weak public institutions; and poor external image, and political instability.